PENGARUH LINGKUNGAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN RUMAH SAKIT JIWA TAMPAN PEKANBARU - Laura Florensia Gultom; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to determine how much influence the work environment and career development have on job satisfaction of the Pekanbaru Tampan Mental Hospital employees. Work Environment as a variable (X1), Career Development as a variable (X2), and Job Satisfaction as a variable (Y). The method in this study is descriptive and quantitative using the SPSS ver 23 for windows program, where the sample in this study was taken as many as 40 respondents and the technique used was census. From the results of data analysis which includes validity test, reliability test, simple linear regression test, multiple linear regression test, determination test, t test, and f test. So it can be concluded that the work environment has a significant effect on employee job satisfaction. Career development has a significant effect on employee job satisfaction. Work environment and career development has an effect on job satisfaction of employees of the Pekanbaru Tampan Mental Hospital. Keywords: Work Environment, Career Development, Job Satisfaction